Nutraceutical and Functional Food Processing Technology. - Boye, Joyce I. (Hoboken : Wiley, 2014)
For several years, the food industry has been interested in identifying components in foods which have health benefits to be used in the development of functional food and nutraceutical products. Examples of these ingredients include fibre, phytosterols, peptides, proteins, isoflavones, saponins, phytic acid, probiotics, prebiotics and functional enzymes. Although much progress has been made in the identification, extraction and characterisation of these ingredients, there remains a need for ready and near-market platform technologies for processing these ingredients into marketable value-add.
6.4 Regulatory Considerations with Respect to Ingredients and Claims6.5 Desired Functional Benefits and Bioactive Ingredients; 6.6 Health Issues Addressable through Functional Beverages; 6.7 Beverage Processing Technology; 6.8 Packaging; 6.9 Other Marketing Considerations; 6.10 Conclusion; References; Chapter 7: Incorporation of Nutraceutical Ingredients in Baked Goods; 7.1 Introduction; 7.2 Bakery Products; 7.3 Nutraceuticals and Nutraceutical- Incorporated Baked Goods; 7.4 Conclusion; References.
Print version record.
Chapter 8: New Technologies in the Processing of Functional and Nutraceutical Cereals and Extruded Products.
Includes bibliographical references and index.
Keywords: Food additives; Functional foods; Nutrition; Food industry and trade